Expression of LAIR-1 (CD305) on Human Blood Monocytes as a Marker of Hepatic Cirrhosis Progression - María Martínez-Esparza; Antonio José Ruiz-Alcaraz; Violeta Carmona-Martínez; María Dolores Fernández-Fernández; Gonzalo Antón; María Muñoz-Tornero; Miriam Lencina; Inmaculada Pagán; Jesús de la Peña; Pilar García-Peñarrubia (Journal of Immunology Research)
Background and Aim. The presumed role of the inhibitory receptor LAIR-1 (CD305) in the inflammatory response suggests that it might contribute to the pathophysiology of chronic inflammatory diseases such as liver cirrhosis. We studied the LAIR-1 expression on liver macrophages and blood monocytes related to the progression of liver cirrhosis. Methods. The expression of LAIR-1 was analyzed by immunohistochemistry, flow cytometry, and Western blot. Results. We found a decreased number of macrophages expressing LAIR-1 in cirrhotic liver that could be due to a high presence of collagen, ligand of LAIR-1, in the fibrotic tissue which could downregulate its expression or interfere with the immunostaining. The expression of LAIR-1 decreased after cell differentiation, and the total content, but not the cell surface expression, increased after activation in the HL-60 human macrophage in vitro model. Blood monocytes exhibited higher LAIR-1 expression levels in cirrhotic patients, which were evident even in early clinical stages in all monocyte subsets, and greater in the “intermediate” inflammatory monocyte subpopulation. The in vitro activation of human blood monocytes did not increase its expression on the cell surface suggesting that the in vivo increase of LAIR-1 must be the result of a specific combination of stimuli present in cirrhotic patients. This represents an exclusive feature of liver cirrhosis, since blood monocytes from other chronic inflammatory pathologies showed similar or lower LAIR-1 levels compared with those of healthy controls. Conclusions. These results may indicate that monocyte LAIR-1 expression is a new biomarker to early detect liver damage caused by chronic inflammation in liver cirrhosis.